2023
DOI: 10.1172/jci.insight.163360
|View full text |Cite
|
Sign up to set email alerts
|

A miRNA/CXCR4 signaling axis impairs monopoiesis and angiogenesis in diabetic critical limb ischemia

Abstract: Patients with peripheral artery disease (PAD) and diabetes have the highest risk of critical limb ischemia (CLI) and amputation, yet the underlying mechanisms remain incompletely understood. MicroRNA (miRNA)-sequencing of plasma from diabetic patients with or without CLI was compared to diabetic mice with acute or subacute limb ischemia to identify conserved miRNAs. miRNA knockout mice on high fat diet were generated to explore impact on CLI. Comparison of dysregulated miRNAs from diabetic human subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 60 publications
(80 reference statements)
1
11
0
Order By: Relevance
“…37 C57BL/6 mice with global deficiency in alleles miR-181a2b2 had significantly worse recovery of blood supply following HLI induction compared to wild type controls. 37 Bone marrow transplant and cell specific transgenic studies suggested that miR-181 deficiency impaired Ly6Chi monocyte mobilisation from the bone marrow without local effects in endothelial cells. The impairment in blood flow recovery and the density of new capillaries in these mice could be rescued by infusion of Ly6Chi monocytes, illustrating the importance of these cells in angiogenesis.…”
Section: Promoting Mobilisation Homing and Differentiation Of Bone Ma...mentioning
confidence: 88%
See 3 more Smart Citations
“…37 C57BL/6 mice with global deficiency in alleles miR-181a2b2 had significantly worse recovery of blood supply following HLI induction compared to wild type controls. 37 Bone marrow transplant and cell specific transgenic studies suggested that miR-181 deficiency impaired Ly6Chi monocyte mobilisation from the bone marrow without local effects in endothelial cells. The impairment in blood flow recovery and the density of new capillaries in these mice could be rescued by infusion of Ly6Chi monocytes, illustrating the importance of these cells in angiogenesis.…”
Section: Promoting Mobilisation Homing and Differentiation Of Bone Ma...mentioning
confidence: 88%
“…35 A number of studies have also implicated microRNAs (miRs) in controlling bone marrow cell contribution to angiogenesis and arteriogenesis. 36,37 Cheng and colleagues studied miRs in patients with PAD and mice models of acute HLI secondary to Femoral artery ligation (FAL) and more gradual HLI secondary to placement of ameroid constrictors around the femoral artery (Supplement Figure 2). 36,37 They identified 22 miRs including three of the four members of the miR-181 family (miR-181a-5p, miR-181b-5p and miR-181c-5p) that were downregulated in the plasma of both patients with diabetes and PAD, and mice with HLI.…”
Section: Promoting Mobilisation Homing and Differentiation Of Bone Ma...mentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of human subjects are found in Supplemental Table 1. All human patient samples (25,50) conform to the principles outlined in the Declaration of Helsinki.…”
Section: Human Samplesmentioning
confidence: 99%